Effect of Cadmium on the population growth of the marine diatom Chaetoceros gracilis Schutt - Vera, Giovana (2001)
Phytoplankton constitutes the base of the trophic webs in the marine environment, so it is important to know the possible effects of pollutants on the algal populations. In the present paper the effect of cadmium on the population growth of the diatom Chaetoceros gracilis was assessed. The microalgae were cultured in the a modified “f/2” Guillard medium, and were exposed to different concentrations of cadmium between 50 and 100000 µg.–1, which produced an inhibitory effect from 20% to 99% on the population growth of Chaetoceros gracilis. Based on the dose (cadmium)-response (inhibition) relationship, a mean effective concentration (EC50%) equal to 591 µg.L–1 of cadmium was obtained.